Clinical features and prognostic factors of children with profound sudden sensorineural hearing loss - Xiao, Ling; Su, Shuping; Liang, Jia; Jiang, Ying; Shu, Yan; Yao, Hongbing; Ding, Ling (Frontiers in Pediatrics, 2022)
Objective: To investigate the clinical features of children with sudden sensorineural hearing loss (SSNHL) with the profound audiogram pattern and factors affecting the prognosis. Methods: We retrospectively analyzed the clinical data of 147 children with SSNHL with the profound audiogram pattern who received inpatient treatment at our department from January 2016 to January 2021. All children were administered with systemic steroid therapy and/or intratympanic steroid (ITS) treatment for 2 weeks. Statistical analyses were performed for the clinical features, treatment effectiveness, and factors affecting the prognosis using SPSS 23.0. Results: The median age of the study population was 8 (6–10) years. The median treatment onset time was 8 (4–20) days. The most common symptom was tinnitus (45.58%). Laboratory findings showed abnormal leukocyte and platelet counts and cytomegalovirus and Epstein–Barr (EB) virus IgG antibodies in 25.85%, 17.01%, 36.73%, and 41.50% of the children, respectively. The overall recovery rate of the treatment was 20.04%. The univariate analysis showed that age, treatment onset time, tinnitus, and ITS treatment were associated with the prognosis (p<0.05).Regarding laboratory findings, the neutrophil count, lymphocyte count, and neutrophil-to-lymphocyte ratio differed significantly between the effective and invalid treatment effect groups (p < 0.05).The multivariable logistic regression analysis showed that treatment onset time (odds ratio [OR] = 0.936, 95% confidence interval [CI]: 0.881–0.994) and ITS treatment (OR = 0.174, 95% CI: 0.044–0.0687) correlated with hearing recovery (p < 0.05). Conclusions: The earlier the treatment start time of children with SSNHL with the profound audiogram pattern, the better the prognosis. Further, ITS is an effective treatment option.